POPULAR MARKETS: FROM FUTURE STUDIES TO THE DEVELOPMENT OF PRODUCTS - Silva, Antonio Thiago Benedete da (Future Studies Research Journal: Trends and Strategies, 2009)
Strategies for running companies in low-income markets have been in the spotlight in both the academic and the corporate environments. However, the first discussions about the relevance of such markets arose during the 1980s, when scenario-prospecting studies showed that popular markets would provide many opportunities around the year 2000. Indeed, at present, the base of the pyramid has many unaddressed needs that offer business possibilities for those companies that are willing to review their strategies. In this context, product development becomes increasingly important, since products targeting consumers of the C, D and E classes may need different features from those of goods manufactured for the A and B classes. The aim of this study is to revisit past popular market forecasts and to identify development trends for goods that target low- income consumers. Our results indicate that Wright and Johnson’s (1984) studies predicted that Brazil would maintain both qualitative and quantitative progress in its socioeconomic development over the next two decades and that the development of popular products is undergoing a buoyant phase. Several functional perspectives were used to develop an understanding of the phenomenon, especially marketing, engineering and manufacturing. Key words: Future studies. Popular markets. Product development.